Pendidikan Islam dalam Lingkup Dimensi Sosio Kultural di Era Revolusi Industri 4.0 - Ahyani, Hisam; Permana, Dian; Abduloh, Agus Yosep (Prodi PAI STAI Sumatera Medan, 2020)
This study aims to analyze Islamic education within the socio-cultural and Islamic education dimensions in responding to the challenges of the industrial revolution era 4.0. This study uses a library research method. The results showed that in the scope of the socio-cultural dimension, Islamic education serves as a forum that can instill tolerance, prevent radicalism, and think moderately. Islamic education is also an instrument that can face the challenges of the this era, because unique personality development is the reason for the ability of Islamic education to survive in the era of the industrial revolution 4.0. In relation to responding to the challenges of the industrial revolution era 4.0 of Islamic education, Islamic education will not be overlooked by the negative values ​​of the impact of the this era, because Islamic education maintains strong values ​​that come from the Al-Qur'an and Hadith. In addition, Islamic education does not close itself to technological sophistication, thus opening access to higher development and adapting to the needs of society. In addition, Islamic education is also not only oriented to worldly values ​​but believes in ukhrawi values, which function as one's spiritual strength, which in this digital era spiritual values ​​are starting to be abandoned.